N27 Group meetings for adolescents with IBD: results of a survey on patients’ interests - S Gigante; A Cerizza; K Pozzi; R I Comoretto; M Martinato (Journal of Crohn's and Colitis, 2024)
Abstract Background The increase in both the incidence and prevalence of IBD, especially in people under 21 years of age1,2,3 outlines new issues to be considered in caring for these patients, like the psychosocial effects on both adolescents and their families, school absences, and developmental delay2. The need for better support to improve their HRQoL4, the embarrassment related to the disease, the anxiety about a sudden appearance of gut symptoms, frequent hospital admissions, and diet restrictions, can lead to social isolation5,6. Group meetings designed to make adolescents and young adults with IBD meet each other and with healthcare professionals (HCP) who are experts in IBD can create a safe environment in which to discuss fears, everyday problems and possible solutions, and any doubt about their condition. This could also provide support, suggestions, and opportunities to peer-compare, further promoting social relationships. This study investigated their willingness to participate in this experience and what they consider important to discuss. Methods A focus group involving HCP from a paediatric gastroenterology clinic and interviews with a sample of patients provided the basis on which a clear and easy-to-understand survey was developed concerning interest in the project, willingness to participate, topics to be discussed, and needs of peer relationship. The survey was then performed collecting anonymous data to avoid any kind of potential bias. Results Twenty-two patients aged 14 to 19 years completed the survey, showing their poor occasions of discussion about the disease and its related issues with other patients (54.5% of them do not know people with IBD) even if they can talk with their family, HCP and peers outside the hospital or outpatient clinic settings (tab 1). The willingness to participate in a group meeting is higher in the oldest subjects, and they show the highest interest in a peer relationship with patients of the same age and expert HCP. The topics considered more significant are 'nutrition' and 'mood' (described by almost two-thirds of patients) followed by ‘symptoms’ and ‘social life’ (fig 1). The best meeting schedule from the patient's point of view is every 6-8 weeks, with both in-person and virtual participation. Conclusion This study provides useful information on the feasibility and willingness of young patients with IBD to participate in such interventions. After the experimental application of group meetings, it will be mandatory to let patients provide feedback on this activity and to assess their effects on patients’ psychosocial well-being. References (DOI) 1 10.1016/j.crohns.2013.01.010 2 10.1053/j.gastro.2021.12.282 3 10.1016/j.gtc.2023.05.001 4 10.1093/ibd/izy041 5 10.1007/s10880-021-09778-0 6 10.1111/hsc.13755